Influence of sowing dates and weed management on weed growth and nutrients depletion by weeds and uptake by chickpea (Cicer arietinum) under rainfed condition - SINGH, R P; VERMA, S K; SINGH, R K; IDNANI, L K (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted at BHU, Varanasi during rabi season of 2009-10 and 2010-11 to find out effect of sowing dates and weed management on weed growth, yield attributes, yield and nutrient uptake by weeds and chickpea (Cicer arietinum L.) under rainfed conditions. The results revealed that early sowing (10 November) significantly reduced the weed density and its dry matter. Among different weed management treatments, sequential application of pendimethalin (1 kg/ha pre-em) followed by quizalofop (50g/ha post-em) recorded the lowest density and dry weight of weeds. Crop sown at 10 November recorded significantly lowest nutrient depletion by weeds and highest yield and nutrients uptake by chickpea. Significantly lowest nutrient depletion by weeds and highest growth parameters, yield attributes, yield and nutrients uptake by chickpea were recorded under sequential application of pendimethalin (1 kg/ha pre-em) followed by quizalofop (50g/ha post-em). Regression equations revealed that unit increase in weed control efficiency increased the grain and straw yields, respectively by 13.67 and 32.74 kg/ha.